Electronic Portfolio Assessment Strategy Using Google Classroom to Improve Students’ Abilities in Learning Chemistry - Nuryanto; Nahadi (Jurnal Penelitian Pendidikan IPA, 2023)
This research aims to determine electronic portfolio assessment strategies using Google Classroom to improve students' abilities in learning chemistry. Assessment is an important aspect of learning to measure students' abilities. Characteristics of chemical material that contains calculations and concepts and has connections between concepts, requires the ability to master concepts and critical thinking skills of students in learning chemistry. Electronic portfolio assessment using Google Classroom is one of the uses of technology in the field of education. The method used in this research is a survey method. This research involved ten (10) high school chemistry teachers from various schools in Sumedang Regency. The data collection technique uses a questionnaire with qualitative data type. The research results show that teachers have implemented various types of assessment in chemistry learning. However, only 70% of teachers have implemented electronic portfolio assessment and it is not optimal. In using chemistry learning media, all teachers have used the application Google Classroom. In terms of students' abilities, both the ability to master chemical concepts and critical thinking skills are still quite low. The conclusion in this research is an electronic portfolio assessment using Google Classroom can be an alternative to improve students' abilities in learning chemistry.